The heart never forgets - Otaru, Ana (Atheneum Books for Young Readers, 2024)
"A young girl pays tribute to the memory of her grandfather during a West African masquerade festival in this moving, lushly illustrated picture book. "DUM! DUM! DUM! DUM! / The talking drums thump a sweet beat ... / The masquerade has begun." As villagers gather to hear masked musicians beating drums, savor fried plantains, and watch the joyful dancers, a young girl joins the celebration with her family. But this year, everything feels different; it's the first masquerade without Grandpa. Each member of the family carries something that honors Grandpa--his clanking beads, soft velvet hat, and carved walking stick. But the young girl doesn't have any of Grandpa's items. Instead, she brings with her a special memory shared only between the two of them. Will she be able to share it with the world?"--